Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kecematan Monta Kabupaten Bima - M Agil Saputra; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The work environment is the situation around the workplace both physically and non-physically which can give the impression of being pleasant, secure, reassuring and the impression of being at home/at ease at work and so on. Observations made by researchers at the Monta District Office, Bima Regency, show that some of the performance of employees at this office is not fully in accordance with what is expected by the organization in general. Dealing with such complex tasks, functions and authorities, the office should need human resources who have high performance at workThe research approach used in this study is to use an associative approach. The results showed that: 1. Work motivation and work environment simultaneously influence employee performance at the Monta District Office, Bima Regency 2. Work motivation influences employee performance at the Monta District Office, Bima Regency 3. The work environment influences employee performance at the Monta District Office Bima districtKeywords: work motivation, work environment, employee performance